Microencapsulation of Nigella sativa oleoresin by spray drying for food and nutraceutical applications. (1st August 2016) - Edris, Amr E.; Kalemba, Danuta; Adamiec, Janusz; Piątkowski, Marcin
Highlights: The oleoresin of Nigella sativa seeds was extracted using hexane at room temperature. The oleoresin was emulsified in gum Arabic/maltodextrin encapsulating solution. The emulsion was encapsulated by spray drying into a free flowing powder. Encapsulation efficiency of the oleoresin ranged between 84.2% and 96.2%. The oleoresin powder can be used in fortification of different food and nutraceutical applications. Abstract: Oleoresin of Nigella sativa L. (Black cumin) was obtained from the seeds using hexane extraction at room temperature. The oleoresin was emulsified in an aqueous solution containing gum Arabic/maltodextrin (1:1 w/w) and then encapsulated in powder form by spray drying. The characteristics of the obtained powder including moisture content, bulk density, wettability, morphology, encapsulation efficiency were evaluated. The effect of the spray drying on the chemical composition of the volatile oil fraction of N . sativa oleoresin was also evaluated using gas chromatographic–mass spectroscopic analysis. Results indicated that the encapsulation efficiency of the whole oleoresin in the powder can range from 84.2 ± 1.5% to 96.2 ± 0.2% depending on the conditions of extracting the surface oil from the powder. On the other hand the encapsulation efficiency of the volatile oil fraction was 86.2% ±4.7. The formulated N. sativa L. oleoresin powder can be used in the fortification of processed food and nutraceuticals.